Refleksi Adat Istiadat Masyarakat Sentani Melalui Cerita Terjadinya Danau Sentani - Muntihanah Muntihanah (Balai Bahasa Provinsi Papua, 2019)
Departing from the fiction including the view that folklore is not born from nothing, reflecting sosial customs Sentani contained in the stories legends of Lake Sentani occurrence in trying to decribed. Reflections customs in the story are examined using structural and sociological theory. By combining both theories, can be found reflection in the community mores Sentani a form of power a leader who termed ondofolo so vast and majestic, the concept of social decorum (in term of eating) in the family, the function, and position in society bracelets accessories Sentani.